Information Decentralization in the Digital Era: Analysis of the Influence of Blockchain Technology on E-Journal Applications Using SmartPLS - Faturahman, Adam; Rahayu, Sri; Triyono; Wijaya, Surta; Ayu Sanjaya, Yulia Putri (Blockchain Frontier Technology, 2024)
This research explores the latest in information decentralization using blockchain technology in e-journal applications. Using a Partial Least Squares Structural Equation Modeling (PLS-SEM) approach via SmartPLS, this research integrates variables such as Data Security (KD), Information Transparency (IT), and User Participation (PP) to measure the direct and indirect influence ofblockchain technology . Data was collected from 250 respondents consisting of researchers, developers and end users of e-journals. Analysis shows that Data Security (KD) plays an important role in increasing Information Transparency (IT) with a path coefficient value of 0.75. Furthermore, Information Transparency (IT) significantly influences User Participation (PP) with a pathcoefficient value of 0.65. These results suggest that blockchain implementation not only improves data security, but also facilitates greater transparency, which in turn increases user participation in e-journals. This research makes an important contribution to the literature by showing how specific variables can be leveraged to optimize the application of blockchain technology in the context of e-journals.